Comparative efficacy of platelet-rich plasma and dextrose prolotherapy for stifle joint arthritis in a rabbit model - Fawad Khalil; Hamid Akbar; Muhammad A. Hayat; Hamad B. Rasheed; Sadaf Aslam; Ayesha Safdar; Fiaz Ahmad; Hafiz M. Ahmad; Muhammad T. Sajjad (Iraqi Journal of Veterinary Sciences, 2023)
This study aimed to investigate the efficacy of PRP and dextrose PRL in stifle joint arthritis in rabbits.Sixteen healthy adult male rabbits were allocated into groups A (n=8) and B (n=8). After induction of arthritis in all experimental animals, the animals of group A were treated with intra-articular injection of PRP, while the animals of group B were treated with dextrose PRL. Pain scoring was evaluated by the Simple Descriptive Pain scale at 0d, 6d, 13d, and 19d, while radiographic scoring was examined by Kellgren and Lawrence grading system at pre-induction, post-induction, and post-treatment. The hematological parameters, including PLT, HB, WBC, PCV, RBC, monocytes, and lymphocytes, were assessed in blood samples at 0d, 6d, 13d, and 19d. We observed that Pain scoring showed a significantly lower (P<0.05) value in group A than in group B at 13d and 19d. Radiographic scoring was significantly lower (P<0.05) in group A than the group B during post-treatment. However, during the pre- and post-monoiodoacetate (MIA) induction, there was no significant difference (P>0.05) in radiographic scoring between both groups. The PLT concentration was increased, and monocyte was decreased in the group A animals than the group B animals at 13d and 19d (P<0.05), while WBC, RBC, PCV, HB, and lymphocyte concentration showed no significant difference (P>0.05) between both groups. In conclusion, the application of PRP is an effective method for treating stifle joint arthritis compared to the dextrose PRL in the rabbit model.